Edukasi Penyuluhan pada Ibu Postpartum mengenai Pijat Oksitosin di Ruang Namirah RSU Assalam Gemolong - Paramastri Sita Nabila; Yeni Puji Astuti; Az'zahro Syal Sabillah; Iyyana Al Fiatur Rofiqoh; Oktaviani Layli Kristinawati; Nora Herawati; Husnul Khotimah; Ririn Hestiana Dewi (Lembaga Pengembangan Kinerja Dosen, 2026)
Colostrum, the first breast milk, contains IgA antibodies, proteins, vitamin A, and anti-infection components that are essential for building the baby's immunity, especially against gastrointestinal infections such as diarrhea. The production of colostrum varies between mothers and is influenced by the frequency and strength of the baby's sucking in the early days. Oxytocin massage on the back can stimulate oxytocin and prolactin hormones, aiding the release and increasing the production of breast milk, as well as providing a relaxing effect on the mother. This method can improve the breastfeeding process. The goal of this community service is to explain the benefits of colostrum as a source of immunity for the baby through IgA antibodies and essential nutrients, as well as to demonstrate oxytocin massage as an effective method to enhance milk release and production. The method used is a lecture with leaflet media, which is effective for delivering information. The results show that many postpartum mothers do not understand the benefits of oxytocin massage, which can hinder milk release. Counseling through lectures, discussions, demonstrations, leaflets, and educational videos successfully increased mothers' understanding of oxytocin massage, which can help with relaxation, support uterine involution, and improve milk production and release. This knowledge is expected to be applied in postpartum breastfeeding practices.